CeO2-TiO2 as a Visible Light Active Catalyst for the Photoreduction of CO2 to Methanol - Hamidah, Abdullah; Khan, Maksudur R.; Manoj, Pudukudya; Zahira, Yaakob; Nur Aminatulmimi, Ismail (Elsevier Ltd, 2015)
The performance of CeO2-TiO2 photocatalyst for the photocatalytic reduction of CO2 into methanol was studied under visible light irradiation. The as-prepared catalysts were characterized for their structural, textural and optical properties using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), nitrogen physisorption analysis, UV-vis spectroscopy and photoluminescence (PL) spectroscopy. The characterization results indicated that the presence of CeO2 stabilized the anatase phase of TiO2, decreased its crystallite size, increased the surface area, reduced the band gap energy and lowered the rate of electron-hole pair recombination. The CeO2-TiO2 photocatalyst showed an increased methanol yield of 18.6 µmol/g under visible light irradiation, compared to the bare TiO2 (6.0 µmol/g).